Aedes (Ochlerotatus) communis - Khalin, A. V.; Aibulatov, S. V. (Zenodo, 2021)
Aedes ( Ochlerotatus ) communis (De Geer, 1776) Northernmost records (Fig. 2f). 69°56 ′ 53.88 ″ N, 31°56 ′ 45.03 ″ E, MP, Pechenga Distr., Vayda-Guba (Natvig, 1948); 72°22 ′ 24 ″ N, 52°43 ′ 00 ″ E, AP, Novaya Zemlya, Malye Karmakuly, 25.VI.1900 (MOC); 67°29 ′ 50.68 ″ N, 64°3 ′ 39.93 ″ E, Komi, Vorkuta Distr., Vorkuta (Panyukova & Ostroushko, 2017). Distribution . NWR: AP, Komi, LP, MP, NAR, NP, PP, RK, SPb, VP. Adjacent countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania and Belarus. Europe (ranging northward to the UK, Belgium, the Netherlands and Denmark); the Holarctic. Published as part of Khalin, A. V. & Aibulatov, S. V., 2021, Northernmost records of mosquito species (Diptera: Culicidae) in northwestern Russia, pp. 46-63 in Zoosystematica Rossica (Zoosyst. Rossica) (Zoosyst. Rossica) 30 (1) on page 53, DOI:10.31610/zsr/2021.30.1.46, http://zenodo.org/record/10124237